Different types of electrospun nanofibers and their effect on microfluidic‐based immunoassay. (16th January 2019) - Mahmoudifard, Matin; Vossoughi, Manouchehr; Soleimani, Masoud
Abstract : Protein capturing on polymeric substrate of microfluidic devices is a key factor for the fabrication of immunoassay with high sensitivity. In this work, simple and versatile technique of electrospinning was used to produce electrospun nanofibrous membranes (e.NFMs) with high surface area as a substrate for microfluidic‐based immunoassay to increase sensitivity. It was found that the simultaneous use of e.NFM and 1‐Ethylethyl‐3‐(3‐dimethylaminopropyl)‐carbodiimide/N‐Hydroxysuccinimide hydroxysuccinimide as coupling agent has synergic effect on antigen immobilization onto the microchannels. It was found that the oxygen plasma technique for the creation of oxygen containing functional group like carboxyl and hydroxyl causes extreme leakage of solution through the microchannels. Thus, due to capillary effect, it is impossible to use hydrophilic substrate to modify microchannels. In order to compensate this problem, it is propose to utilize other type of polymer for the fabrication of nanofiber to answer this important question that if it is possible to enhance the sensitivity of immunoassay just by changing the polymer type? For this purpose, four different polymers, namely, polycaprolactone, poly lactic‐co‐glycolic acid, poly L‐lactic acid, and polyethersolfone were used as the based material for e.NFM fabrication. Results showed that compared with plain poly (dimethylsiloxane) surface of microchannels, poly lactic‐co‐glycolic acidand poly L‐lactic acid, which inherently contain end‐group of carboxyl in their chemical structure, can improve the protein immobilization, which leads to immunoassay signal enhancement through 1‐ethyl‐3‐(3‐dimethylaminopropyl)‐carbodiimide/N‐hydroxysuccinimide coupling chemistry, significantly.